Hypertension Pharmacological Treatment in Adults: A World Health Organization Guideline Executive Summary. Issue 1 (15th November 2021) - Al-Makki, Akram; DiPette, Donald; Whelton, Paul K.; Murad, M. Hassan; Mustafa, Reem A.; Acharya, Shrish; Beheiry, Hind Mamoun; Champagne, Beatriz; Connell, Kenneth; Cooney, Marie Therese; Ezeigwe, Nnenna; Gaziano, Thomas Andrew; et al.
Abstract : Hypertension is a major cause of cardiovascular disease and deaths worldwide especially in low- and middle-income countries. Despite the availability of safe, well-tolerated, and cost-effective blood pressure (BP)-lowering therapies, <14% of adults with hypertension have BP controlled to a systolic/diastolic BP <140/90 mm Hg. We report new hypertension treatment guidelines, developed in accordance with the World Health Organization Handbook for Guideline Development. Overviews of reviews of the evidence were conducted and summary tables were developed according to the Grading of Recommendations, Assessment, Development, and Evaluations approach. In these guidelines, the World Health Organization provides the most current and relevant evidence-based guidance for the pharmacological treatment of nonpregnant adults with hypertension. The recommendations pertain to adults with an accurate diagnosis of hypertension who have already received lifestyle modification counseling. The guidelines recommend BP threshold to initiate pharmacological therapy, BP treatment targets, intervals for follow-up visits, and best use of health care workers in the management of hypertension. The guidelines provide guidance for choice of monotherapy or dual therapy, treatment with single pill combination medications, and use of treatment algorithms for hypertension management. Strength of the recommendations was guided by the quality of the underlying evidence; the tradeoffs between desirable and undesirable effects; patient's values, resource considerations and cost-effectiveness; health equity; acceptability, and feasibility consideration of different treatment options. The goal of the guideline is to facilitate standard approaches to pharmacological treatment and management of hypertension which, if widely implemented, will increase the hypertension control rate world-wide.